2006
DOI: 10.1111/j.1365-2621.2006.tb15627.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Apple Juice Foams for Foam-mat Drying Prepared with Egg White Protein and Methylcellulose

Abstract: ABSTRA ABSTRA ABSTRA ABSTRA ABSTRACT CT CT CT CT: I : I : I : I : Intr ntr ntr ntr ntrinsic stability and r insic stability and r insic stability and r insic stability and r insic stability and rheological pr heological pr heological pr heological pr heological proper oper oper oper operties of apple juice foams for foam mat dr ties of apple juice foams for foam mat dr ties of apple juice foams for foam mat dr ties of apple juice foams for foam mat dr ties of apple juice foams for foam mat drying w ying w ying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 25 publications
6
66
0
1
Order By: Relevance
“…But after the initial decrease, a slight increase in foam density was noticed in GMS-MC stabilized foams after 2 min of whipping. Raharitsifa et al (2006) also reported that density of foams decreased with whipping time up to a minimum and increased thereafter probably because excessive whipping (overbeating) could cause foam to collapse. Too high a degree of aeration, thinning of the liquid film between the foam bubbles and mechanical deformation can all lead to rupture of the bubble wall structure Falade et al (2003).…”
Section: Fdmentioning
confidence: 94%
See 1 more Smart Citation
“…But after the initial decrease, a slight increase in foam density was noticed in GMS-MC stabilized foams after 2 min of whipping. Raharitsifa et al (2006) also reported that density of foams decreased with whipping time up to a minimum and increased thereafter probably because excessive whipping (overbeating) could cause foam to collapse. Too high a degree of aeration, thinning of the liquid film between the foam bubbles and mechanical deformation can all lead to rupture of the bubble wall structure Falade et al (2003).…”
Section: Fdmentioning
confidence: 94%
“…Falade et al (2003) used GMS and egg albumin for foam-mat drying of cowpea. Raharitsifa et al (2006) used egg white and methylcellulose as a foaming additive for characterization of apple juice foams for foam-mat drying and optimized their levels to 2-3% and 0.2%, respectively, to obtain stable foams. Muthukumaran et al (2008) dried egg white in freeze drier by foam-mat drying technology using different foam stabilizers (MC, propylene glycol alginate, and xanthan gum) and reported that 0.125% xanthan gum gives sufficient stability.…”
Section: Introductionmentioning
confidence: 99%
“…1, basing on the foam density (ρ f ) previously calculated. This equation is valid if the air density is neglected in relation to the liquid density (ρ l ) (Raharitsifa et al 2006). In the current work, the juice's densities were determined as 1.054 g·cm −3 (YJ) and 1.122 g·cm −3 (CYJ).…”
Section: Air Volume Fractionmentioning
confidence: 97%
“…The stability test consisted of evaluating the volume of liquid drained in a period of 120 min for each foam (Raharitsifa et al 2006). The stability index was calculated using Eq.…”
Section: Physical Stabilitymentioning
confidence: 99%
“…Beating time affects the content of volatile compounds and, the longer the beating time, the greater the losses of these compounds (Thuwapanichayanan et al, 2012). Prolonged beating time can be excessive, leading to collapse of foam structure (Raharitsifa et al, 2006). Table 2 shows the mean values and standard deviations of the characterization of whole myrtle pulp and the selected foam (F1).…”
Section: = − −mentioning
confidence: 99%